Environmental vulnerability in Italian mountain areas and its socioeconomic drivers - Cavallo, Aurora; Cannata, Giovanni; Mastronardi, Luigi; Romagnoli, Luca (Italian Review of Agricultural Economics, 2025)
Mountain areas are exposed to multiple risks due to the complex interactions between environmental, social, and economic factors. This paper aims to assess the environmental vulnerability of mountain areas through a synthetic indicator and to identify the drivers of such vulnerability at the local level. It uses a multidimensional and spatial approach to define the main dimensions of vulnerability based on municipal data. Furthermore, a geographically weighted regression model is used to investigate the drivers of vulnerability. The results show that mountain areas are less environmentally fragile than lowland and hilly regions but have higher demographic, social, and economic vulnerability. However, southern mountains are more fragile due to the lower presence of protected areas and forest cover. The spatial model also reveals a trade-off between environmental preservation and demographic, social, and economic characteristics. These findings should be carefully considered in light of place-based planning strategies and policies in mountain areas, particularly in southern Italy.